2006
DOI: 10.1007/s00441-006-0358-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil depletion retards endometrial repair in a mouse model

Abstract: The contribution of the high abundance of inflammatory cells present in the human endometrium prior to and during menstruation is unknown with respect to endometrial repair and/or menstruation. In this study, the presence and localisation of markers for key inflammatory cells have been examined in a mouse model of endometrial breakdown and repair and the functional contribution of neutrophils has been determined. In the model, decidualisation is artificially induced and progesterone support withdrawn; the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 50 publications
8
68
0
Order By: Relevance
“…The role of resolution mediators in restoration of endometrial tissue homoeostasis leading to scarless healing following menstruation is currently unknown. However, post-menstrual repair is delayed following neutrophil depletion in a mouse model revealing a role for these cells in resolution potentially via LOX enzyme expression (Kaitu'u-Lino et al 2007).…”
Section: Menstrual Functionmentioning
confidence: 99%
“…The role of resolution mediators in restoration of endometrial tissue homoeostasis leading to scarless healing following menstruation is currently unknown. However, post-menstrual repair is delayed following neutrophil depletion in a mouse model revealing a role for these cells in resolution potentially via LOX enzyme expression (Kaitu'u-Lino et al 2007).…”
Section: Menstrual Functionmentioning
confidence: 99%
“…Similar processes have been suggested in the stabilization of murine endometrial blood vessels after menstruation. Neutrophils expressing VEGF are observed in association with angiogenic endothelial cells, and depletion of neutrophils retards endometrial repair (52).…”
Section: Il2rgmentioning
confidence: 99%
“…Neutrophils are present in large numbers during endometrial repair and play an important role. In a mouse model designed to mimic the events of menstruation, it was observed that when neutrophils were depleted, endometrial regeneration was severely affected suggesting that neutrophils along with the regulatory factors they produce contribute to the tissue repair (Kaitu'u-Lino et al, 2007). Macrophages, eosinophils and lymphocytes could also contribute in this process .…”
Section: Reproductive Cyclementioning
confidence: 99%